Prevalensi Penyakit Kanker di Indonesia Berdasarkan Pola Konsumsi Pangan dan Gaya Hidup - Kuswanto Aliwikarta; Nurheni Sri Palupi; Puspo Edi Giriwono (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
Consumption of processed meat is associated to cancer risk increasing. This study used secondary data from RISKESDAS 2013 with a case-control study design, is aimed to analyze the cancer prevelance in Indonesia based on food consumption patterns and lifestyles. The case population is 90 people suffering from cancer and 90 people with no cancer randomly selected as control. Respondent profiles were analyzed by univariate analysis. The relationship of cancer risk factors were analyzed by bivariate analysis and determination of risk factors using multivariate analysis. Sensitivity and specificity analyses showed the cancer vulnerable age is ≥46 years. Processed meat consumption is associated significantly (p=0.000; OR=1.25) in the cancer prevelance. Respondents frequently eat processed meat risk is predicted 1.25 times compared to those not taking. Vegetable consumption (p=0.046; OR=0.509) and fruit consumption (p=0.022; OR=0.365) related significantly to cancer. Vegetables consumption reduce the risk by 0509 times, and fruit consumption reduce the risk by 0365 times. Lifestyle risk factors (physical activity and smoking) significant (p=0.000) to cancer. Multivariate analysis results showed the age, gen- der and processed meat consumption is associated significantly (p=0.000) to cancer.